Pengaruh Penggunaan Gadget Terhadap Perilaku Sosial dan Prestasi Belajar Siswa di Sekolah Dasar - Riswati Ashifa; Yulianti Yulianti; Yona Wahyuningsih (Departement of Mathematics Education, 2022)
This study aims to provide an overview of the Effect of Gadget Use on Social Behavior and Learning Achievement in Social Studies Learning in Elementary Schools. The method we use in this research is descriptive qualitative. This descriptive research is based on the results of the relevant data or literature sources that we have collected. Social sciences are subjects that are taught starting from elementary school using social science materials to study human relations as members of society. The results of this study are the use of gadgets in learning can facilitate obtaining information and improve social skills if used wisely. Gadgets have interesting features for students to use in learning so that students have high learning motivation which affects learning achievement. However, on the other hand, gadgets have negative effects such as addiction, and difficulty interacting and communicating well. The efforts made are that gadgets are used for learning purposes, time restrictions, reward, and punishment, as well as teacher and parent cooperation